2015
DOI: 10.1002/nbm.3340
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and optimization of in  vivo human diffusion‐weighted MRS of the corpus callosum at 3T and 7T

Abstract: Diffusion-weighted MRS (DWS) of brain metabolites enables the study of cell-specific alterations in tissue microstructure by probing the diffusion of intracellular metabolites. In particular, the diffusion properties of neuronal N-acetylaspartate (NAA), typically co-measured with N-acetylaspartyl glutamate (NAAG) (NAA + NAAG = tNAA), have been shown to be sensitive to intraneuronal/axonal damage in pathologies such as stroke and multiple sclerosis. Lacking, so far, are empirical assessments of the reproducibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…The high specificity of MRS techniques is provided at the cost of an intrinsic low signal-to-noise ratio (SNR), which is further exacerbated by the addition of diffusion weighting and error propagation in the calculation of diffusion measures. The reproducibility of the model employed here for calculating metabolite diffusion metrics was tested previously in a study investigating the inter-and intra-subject variability of both empirical and modelled diffusion properties of tNAA, and evaluating the optimized protocol to be used in clinically relevant acquisition times in the same region of interest (Wood, et al, 2015). The acquisition scheme employed in this study was carefully evaluated following the guidelines reported in Wood et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high specificity of MRS techniques is provided at the cost of an intrinsic low signal-to-noise ratio (SNR), which is further exacerbated by the addition of diffusion weighting and error propagation in the calculation of diffusion measures. The reproducibility of the model employed here for calculating metabolite diffusion metrics was tested previously in a study investigating the inter-and intra-subject variability of both empirical and modelled diffusion properties of tNAA, and evaluating the optimized protocol to be used in clinically relevant acquisition times in the same region of interest (Wood, et al, 2015). The acquisition scheme employed in this study was carefully evaluated following the guidelines reported in Wood et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility of the model employed here for calculating metabolite diffusion metrics was tested previously in a study investigating the inter-and intra-subject variability of both empirical and modelled diffusion properties of tNAA, and evaluating the optimized protocol to be used in clinically relevant acquisition times in the same region of interest (Wood, et al, 2015). The acquisition scheme employed in this study was carefully evaluated following the guidelines reported in Wood et al 2015. Power calculations in the same study showed that, based on the suggested acquisition scheme, at 7T the minimum number of subjects in each group necessary to detect a 10% difference in D(tNAA), ADC(tNAA) and ADC(tCr) between two groups is 13, 12, and 7, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A diffusion tensor can then be extracted on the basis of S(b)/S(0)=exp[i,jfalse(bijDijfalse)] , where S( b ) and S(0) are signal intensities with and without the diffusion‐sensitizing gradients. When incorporated into MRI measurements these calculations lead to a variety of diffusion tensor imaging (DTI) modalities , of widespread use in preclinical and clinical tractography . Because all DTI modalities aim to represent the effects introduced by random molecular displacements spanning sub‐mm ranges, tissue motions happening on similar length‐scales can harm their performance.…”
Section: Introductionmentioning
confidence: 99%